Fermentabilitas ruminal secara in vitro suplementasi tepung daun gamal, kelor, randu dan sengon dalam konsentrat hijau - Eko Marhaeniyanto; Sri Susanti (Faculty of Animal Science, Universitas Brawijaya, 2018)
The aim of this research was to study the in vitro ruminal fermentability of supplementation of Gliricidia sepium, Moringa oleifera, Lamk (MOL), Ceiba pentandra and Paraserianthes falcataria leaf meal in concentrate feed to be tested on sheep. This research with the experimental methods was arranged in Randomized Block Design (RBD) with 6 treatments and 3 groups. The treatment feed tested consisted of concentrate without leaves and concentrate with leaf meal supplementation. Crude protein content (CP) concentrates were prepared 16%, 18% and 20%. Supplementation uses a mixture of Gliricidia sepium, MOL, Ceiba pentandra and Paraserianthes falcataria leaf meal in concentrate feed (1: 1: 1: 1) as much as 10%, 20% and 30%. The measured variables were degradation of dry matter (DDM) and degradation of organic matter (DOM), gas production rate, microbial biomass and NH3 concentration. The use of mixed leaf meal in concentrate feed resulted in in vitro DDM as well as concentrate feed without leaf meal supplementation. Supplementation of leaf meal in concentrate feed as much as 30% with CP 20% resulted in a decrease in the value of fermentability. The supplementation of leaf meal in concentrate feed as much as 20% in concentrate feed with CP 18% produced the best fermentability value. Suggested for in-vivo trials on sheep using 18% protein concentrate feed by utilizing Gliricidia sepium, MOL, Ceiba pentandra and Paraserianthes falcataria leaf meal in concentrate feed as cheap protein sources.